Time Efficient Virtual Network Embedding Algorithm. Issue 2 (2nd April 2016) - Huang, Tao; Gu, Ying; Liu, Jiang; Liu, Yunjie
Abstract: The virtual network embedding problem is an essential problem in network virtualization. Researchers care about efficiency of the virtual network embedding algorithm. This issue has two procedures: node embedding and link embedding. However, previous studies mainly concentrate on the node embedding while neglecting the link embedding, which is the main cause for the bad running time. In this paper, we propose a new algorithm—Deleting-first algorithm, which deletes incapable substrate links for the current virtual request before link mapping. The efficiency of virtual network embedding will be improved. The simulation results show that the average performance of the new algorithm is better at runtime.